DNA Barcoding of VERBENACEAE Plant Species using ITS2 and RBCL Genes - Bukhari, Imran (2016)
The Verbenaceae refers to a family of vervain which are shrubs or trees and composed of 100 genera and about 2600 species around the world which usually grow in sub-tropical and tropical areas. Due to its wide availability there have been difficulties in differentiating the verbenaceae species based on their morphologies. DNA barcoding while becoming a common method of species identification, has had problems in its use such as the lack of consensus on gene loci and their utility across taxons, as well as methods of analysis. Hence this study tests ITS2 and rbcl for their ability in identification of Verbenacea. The three species used in this experiment are Duranta repens, Lantana camara and Stachytarpheta jamaicensis. The potential barcodes were amplified using polymerase chain reaction followed by sequencing. The sequences were characterized, then similarity (BLAST) and distance analysis (Barcode gap and tree topologies were carried out). The negative barcode gap using rbcl suggests that it is not suitable for identification, although tree topology based on rbcl enabled identification. Conversely, for ITS2 there were barcode gaps between all three species, but the tree topology, especially with combined experimental and downloaded data, did not allow clear identification. Increasing sample size and including samples from different geographic areas, as well as testing other loci is suggested and only the combined effort of scientist around the world will be able to build a comprehensive database, making DNA barcoding a feasible method of species identification.